The Global Evolution of Ecological Communication Studies in Disasters: A Bibliometric Analysis - Muh. Resa Yudianto Suldani; Hermin Indah Wahyuni; P. Wiryono Priyotamtama (PT Mattawang Mediatama Solution, 2023)
The urgency of ecological communication is critical, given the increasingly complex and urgent challenges caused by disasters. The purpose of this research is to evaluate the development of studies on disaster-related ecological communication. This study uses bibliometric analysis, in which the data source comes from the Scopus database. The analysis tool used is Vosviewer. The findings of this study indicate that the number of publications discussing ecological communication in disasters has increased significantly in recent years. The main focus of the research findings includes disaster prevention, risk assessment, climate change, and natural disasters. This research provides important insights into the role of communication in responding to disasters and environmental challenges and building community resilience. Ecological communication research trends in disasters open prospects to expand understanding and develop effective communication strategies to face environmental challenges and disasters in the future. The results of this research can be used as a basis for developing more effective communication strategies in facing environmental challenges in the future.